EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM POSING DAN PROBLEM SOLVING DENGAN PENDEKATAN PMR TERHADAP PRESTASI BELAJAR DAN KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI KREATIVITAS SISWA KELAS VII SMP NEGERI DI KABUPATEN SUKOHARJO - Hodiyanto, Hodiyanto; Budiyono, Budiyono; Slamet, Isnandar (Jurnal Pembelajaran Matematika, 2016)
Abstract: The objective of this research was to investigate the effect of learning models with realistic mathematic education (RME) approach on learning achievement and mathematical communication ability viewed from student creativity. The learning models compared were Problem Posing (PP), Problem Solving (PS) and direct learning models. This research used a quasi-experimental research. The population were the seventh grade students of junior high school in Sukoharjo. The samples of this research were taken by using the stratified cluster random sampling technique. The proposed hypothesis of this research was analyzed by using the two way multivariate analysis of variance with unbalanced cells. The results of the research are as follows: (1) model of PP learning and model of PS learning with RME approach result the same achievement, but model of PP learning with RME approach results in a better mathematical communication ability than model of PS learning with RME. Model of PP learning and model of PS learning with RME approach result in better achievement and mathematical communication ability than direct learning model. (2) the students with the high creativity have better achievement and mathematical communication ability than those with the moderate or low creativity, but the students with the moderate and low creativity have the same achievement and mathematical communication ability. (3) in each creativities of students, model of PP learning and model of PS learning with RME approach result in better achievement and mathematical communication ability than direct learning model. Model of PP learning and model of PP learning with RME approach result the same achievement, but model of PP learning with RME approach results in a better mathematical communication ability than model of PS learning with RME. (4) in each learning models, the students with high creativity have better achievement and mathematical communication ability than those with medium and low creativity, and the students with moderate and low creativity have the same achievement and mathematical communication ability.Keywords: PP Learning, PS Learning, RME Approach, Direct Learning, Mathematical Communication Ability, Achievement, and Creativity of students.